Super-hydrophilic zwitterionic polymer surface modification facilitates liquid transportation of microfluidic sweat sensors - Fu, Fanfan (2022)
The transportation of sweat in an epidermal sweat sensor is critical for the monitoring of biochemical compositions of human sweat. However, it is still a challenge to engineer microfluidic devices with super-wetting channels for such epidermal sweat sensors. Herein, we report a zwitterionic poly (2-methacryloyloxyethyl phosphorylcholine) (PMPC) modified microfluidic device with super-wetting and good liquid transport ability via an azo coupling reaction of PMPC onto the surface of polydimethylsiloxane (PDMS) microfluidic devices. The obtained PMPC modified microfluidic device can be integrated with flexible electrochemical sensor to measure the ion compositions of human sweat in real-time. The super-hydrophilic zwitterionic polymer surface modification can greatly facilitate the transportation of body fluids in microfluidic sensors for the detection of various biomarkers. Such microfluidic sensors have great potential for next generation personalized healthcare.